Cryptosporidiosis Treated With Nitazoxanide in Intestinal Transplantation. Issue 3 (May 2016) - Hand, Jonathan; Huard, Genevieve; Rana, Meenakshi; Moon, Jang; Iyer, Kishore; Patel, Gopi
Abstract : Abstract: In developed countries, infections with Cryptosporidium species are rare and are often associated with waterborne or food-borne outbreaks. There is increasing evidence that solid organ transplant recipients are at increased risk of debilitating cryptosporidiosis in the setting of exogenous immunosuppression. We report a case of cryptosporidiosis, likely acquired through travel, in an intestinal transplant recipient who was successfully treated with nitazoxanide. This case highlights the unique challenges in diagnosis and treatment of immunocompromised patients with cryptosporidiosis, specifically in intestinal transplantation.